Antistatic ink and preparation method thereof
By plating silver quantum dots on the surface of oxygen-doped carbon nitride, the problems of low conductivity and poor dispersion of inorganic semiconductors are solved, and efficient antistatic properties and film-forming capabilities are achieved, which are suitable for multi-color ink systems.
Patent Information
- Application Number
- CN202411366015.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-14
AI Technical Summary
Among the existing antistatic inks, inorganic semiconductors such as carbon nitride and graphite have low conductivity and poor dispersion in solution, which leads to the possibility of destroying the continuity of the ink resin when used in the ink system, reducing adhesion properties and film formation. The ability limits its application in multi-color inks.
Using antistatic inks including UV resin prepolymers, acrylate monomers, butyl acrylate, photoinitiators and surface-plated silver-carbonized nitrogen nanoparticle dispersions, silver-plated quantum dots are plated on the oxygen-doped carbon nitride surface, It forms high conductivity and excellent electron conductivity, and combines appropriate amounts of additives such as leveling agents and defoaming agents to prepare efficient antistatic inks.
It improves the conductivity and film-forming ability of anti-static inks, enhances the adhesion and anti-static properties of inks, and is suitable for multi-color ink systems, and overcomes the problem of large amount of traditional inorganic additives in inks.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of antistatic ink. Background Art
[0002] Graphite is often used as an antistatic agent for inks due to its low price and good conductivity. However, since graphite is black, it is mostly used in black ink systems and is not suitable for other color systems. Carbon nitride has a two-dimensional layered structure similar to graphite, has good conductivity, and is lighter in color, which has little effect on the color of the ink system. It is expected to be used to prepare antistatic inks of various colors.
[0003] However, the conductivity of inorganic semiconductors such as carbon nitride and graphite is much lower than that of organic metals, and their dispersibility in solutions is also poor. Usually, they can only achieve good antistatic properties when used in large amounts in the ink system. However, adding a large amount of such inorganic additives can easily destroy the continuity of the ink resin and reduce the ink's adhesion and film-forming properties. This greatly limits the application of such antistatic agents in inks. Summary of the invention
[0004] The object of the present invention is to solve the problems existing in the prior art and disclose an antistatic ink, which comprises, by weight:
[0005] UV resin prepolymer: 10-20 parts;
[0006] Acrylate monomer: 9-20 parts;
[0007] Butyl acrylate: 8-20 parts;
[0008] Photoinitiator: 0.4-0.7 parts;
[0009] Surface-coated silver carbonitride nanoparticle dispersion: 35-70 parts, wherein the carbonitride is oxygen-doped carbon nitride, the plated silver is silver quantum dots, and there is no organic molecule between the silver quantum dots and the oxygen-doped carbon nitride;
[0010] Other appropriate additives.
[0011] In a preferred embodiment, a surface silver-plated carbon nitride nanoparticle dispersion is prepared by plating silver quantum dots on an oxygen-doped carbon nitride surface through a silver plating step, wherein the silver plating step is to first adsorb silver ions on the oxygen-doped carbon nitride surface, and then generate silver quantum dots in situ on the oxygen-doped carbon nitride surface.
[0012] In a preferred embodiment, the other appropriate amount of additives include a leveling agent, a wetting agent and a defoaming agent.
[0013] The present application also discloses a method for preparing an antistatic ink, the steps of which are as follows:
[0014] S1: preparing UV light-curable resin prepolymer;
[0015] S2: preparing oxygen-doped carbonitride nanoparticles, adding the obtained nanoparticles, tyrosine, and silver ammonia solution into deionized water, gradually adding glucose after ultrasonic dispersion, then ultrasonically dispersing, centrifugally drying, adding ethyl acetate containing polyvinylpyridine, and ultrasonically dispersing to obtain a suspension;
[0016] S3: The prepared UV light-curable resin prepolymer, acrylate monomer, UV photoinitiator, prepared suspension, leveling agent, wetting agent and defoaming agent are mixed in proportion to prepare antistatic UV ink.
[0017] In a preferred embodiment, the method for preparing a UV light-curing resin prepolymer is as follows: add measured amounts of polyethylene glycol, polypropylene glycol, 2,2-dihydroxymethylpropionic acid, isophorone diisocyanate and dibutyltin dilaurate into a container, slowly heat the container to 80°C while stirring, and react at a constant temperature for 6 hours; then cool the container to 60°C, add measured amounts of hydroxyethyl acrylate, and react at a constant temperature for 4 hours; then cool the container to room temperature to obtain a UV light-curing polyurethane prepolymer.
[0018] In a specific embodiment, the raw material ratio is as follows:
[0019] Polyethylene glycol: 20-70%
[0020] Polypropylene glycol: 20-70%
[0021] 2,2-Dihydroxymethylpropionic acid: 0.1-2%
[0022] Isophorone diisocyanate: 1-15%
[0023] Dibutyltin dilaurate: 0.1-1.0%
[0024] Hydroxyethyl acrylate: 0.1-2%
[0025] In a preferred embodiment, the method for preparing oxygen-doped carbonized nitrogen nanoparticles is as follows: weigh melamine and put it into a muffle furnace. In the absence of nitrogen protection, heat it to 400°C and react at a constant temperature for 8 hours. After the reaction is completed, reduce the temperature to room temperature to obtain oxygen-doped carbonized nitrogen nanoparticles.
[0026] In a preferred embodiment, the preparation method of the suspension is as follows: oxygen-doped carbon nitride nanoparticles, tyrosine and a 10wt% silver ammonia solution are added to deionized water, ultrasonically dispersed, and then glucose is gradually added. After the addition is complete, ultrasonication is continued, and then centrifugation is performed to obtain a precipitate. The obtained precipitate is vacuum-dried at 60°C, and ultrasonically dispersed in 1000ml of ethyl acetate containing 0.1wt% polyvinylpyridine for 2h to obtain a suspension.
[0027] In a preferred embodiment, the molecular weight of the polyethylene glycol is between 400-2000, and the molecular weight of the polypropylene glycol is between 400-2000.
[0028] In a specific embodiment, the weight ratio of the raw materials of the antistatic ink is as follows:
[0029] UV resin prepolymer: 40-85%;
[0030] Methyl methacrylate: 20-40%;
[0031] Butyl acrylate: 20-40%;
[0032] UV light initiator: 0.1-1%;
[0033] Surface-coated silver carbonitride nanoparticle dispersion: 1-15%;
[0034] Wetting agent: 0.1-1%;
[0035] Defoamer: 0.1-1%
[0036] Leveling agent: 0.1-2%. DETAILED DESCRIPTION
[0037] The present invention is described in detail below.
[0038] 1. Preparation of UV light-curing resin prepolymer.
[0039] In a four-necked flask equipped with a stirrer, a condenser and a thermometer, a measured amount of polyethylene glycol (molecular weight between 400-2000), polypropylene glycol (molecular weight between 400-2000), 2,2-dihydroxymethylpropionic acid, isophorone diisocyanate and dibutyltin dilaurate are added at room temperature, and the temperature is slowly raised to 80°C while stirring, and the reaction is carried out at a constant temperature for 6 hours; then the temperature is lowered to 60°C, and a measured amount of hydroxyethyl acrylate is added, and the reaction is carried out at a constant temperature for 4 hours; then the system is cooled to room temperature to obtain a UV light-curing polyurethane prepolymer.
[0040] The dosage of each substance is shown in Table 1:
[0041] Table 1
[0042]
[0043] Note: 400, 1000 and 2000 in the table represent the molecular weight of the corresponding polymer. The mass unit of each component is g
[0044] 2. Preparation of Carbon Nitride Nanoparticle Dispersion
[0045] Example 1: First, weigh 80.0g of melamine and put it into a muffle furnace. In the absence of nitrogen protection, heat it to 400°C and keep it at this temperature for 8h. After the reaction is completed, cool it to room temperature to obtain a light yellow solid powder. Then, add the obtained powder, 33.55g of tyrosine and 29.44g of 10wt% silver ammonia solution into 1000.0ml of deionized water.
[0046] Ultrasonic dispersion for 2 hours, then gradually add 3.34g glucose, the addition time is 0.5 hours, after the addition is complete, continue ultrasonication for 2 hours, then centrifuge to obtain a precipitate, vacuum dry the precipitate at 60°C, ultrasonically disperse it in 1000ml of ethyl acetate containing 0.1wt% polyvinylpyridine for 2 hours to obtain a suspension, set aside, and ultrasonicate for 1 hour before use. Analysis shows that the surface of the carbonized nitrogen nanoparticles is coated with silver quantum dots, and there are no organic molecules between the silver quantum dots and the carbonized nitrogen nanoparticles.
[0047] Control group 1: First, weigh 80.0g of melamine and put it into a muffle furnace. In the absence of nitrogen protection, heat to 400℃ and react at a constant temperature for 8h. After the reaction is completed, the temperature is lowered to room temperature to obtain a light yellow solid powder. At the same time, 29.44g of 10wt% silver ammonia solution, 100ml deionized water and 33.55g tyrosine were added to a 200ml beaker, and 3.34g of glucose was gradually added under ultrasonic conditions. The addition time was 0.5h. After the addition was complete, the ultrasonic was continued for 2h, and then the silver quantum dot precipitate was obtained by centrifugation. After that, the obtained quantum dot precipitate and oxygen-doped carbon nitride powder were all added to 1000.0ml deionized water, ultrasonically dispersed for 2h, and then centrifuged to obtain a precipitate. After the obtained precipitate was vacuum dried at 60℃, it was ultrasonically dispersed in 1000ml ethyl acetate containing 0.1wt% polyvinylpyridine for 2h to obtain a suspension, which was set aside and ultrasonicated for 1h before use. The surface of carbonized nitrogen nanoparticles is coated with silver quantum dots, and there are organic molecules between the silver quantum dots and carbonized nitrogen nanoparticles.
[0048] Control group 2: First, weigh 80.0g of melamine and put it into a muffle furnace. Under nitrogen protection, heat to 400℃ and react at a constant temperature for 8h. After the reaction, lower the temperature to room temperature to obtain a light yellow solid powder. Afterwards, add the obtained powder, 33.55g of tyrosine and 29.44g of 10wt% silver ammonia solution to 1000.0ml deionized water, ultrasonically disperse for 2h, and then gradually add 3.34g of glucose, the addition time is 0.5h, and after the addition is complete, continue ultrasonication for 2h, and then centrifuge to obtain a precipitate. After the obtained precipitate is vacuum dried at 60℃, ultrasonically dispersed in 1000ml of ethyl acetate containing 0.1wt% polyvinylpyridine for 2h, and set aside. After the ultrasound stops, a precipitate is precipitated, and ultrasound is performed for 1h before use. Analysis shows that the surface of the carbon nitride nanoparticles is coated with silver quantum dots, and there are no organic molecules between the silver quantum dots and the carbon nitride nanoparticles.
[0049] Control group 3: First, weigh 80.0g of melamine and put it into a muffle furnace. Under nitrogen protection, heat it to 400℃ and keep it at constant temperature for 8h. After the reaction is completed, cool it to room temperature to obtain a light yellow solid powder.
[0050] At the same time, 29.44g of 10wt% silver ammonia solution, 100ml of deionized water and 33.55g of tyrosine were added to a 200ml beaker, and 3.34g of glucose was gradually added under ultrasonic conditions. The addition time was 0.5h. After the addition was complete, the ultrasonic was continued for 2h, and then the silver quantum dot precipitate was obtained by centrifugation. After that, the obtained quantum dot precipitate and carbon nitride powder were all added to 1000.0ml of deionized water, ultrasonically dispersed for 2h, and then centrifuged to obtain a precipitate. After the obtained precipitate was vacuum dried at 60°C, it was ultrasonically dispersed in 1000ml of ethyl acetate containing 0.1wt% polyvinylpyridine for 2h. After the ultrasonic was stopped, a precipitate was precipitated. The ultrasonic was performed for 1h before use. It was analyzed that the surface of the carbonized nitrogen nanoparticles was coated with silver quantum dots, and there were organic molecules between the silver quantum dots and the carbonized nitrogen nanoparticles.
[0051] Control group 4: First, weigh 80.0g of melamine and put it into a muffle furnace. Under nitrogen protection, heat to 400℃ and react at constant temperature for 8h. After the reaction, lower the temperature to room temperature to obtain a light yellow solid powder. After that, add the obtained powder, 33.55g of tyrosine, 29.44g of 10wt% silver ammonia solution and 3.34g of glucose to 1000.0ml of deionized water, ultrasonically disperse for 2h, and then centrifuge to obtain a precipitate. After vacuum drying the obtained precipitate at 60℃, ultrasonically disperse it in 1000ml of ethyl acetate containing 0.1wt% polyvinylpyridine for 2h for standby use. After the ultrasound stops, a precipitate is precipitated. Ultrasonicate for 1h before use. After analysis, the surface of the carbonized nitrogen nanoparticles is coated with a silver layer.
[0052] 3. Preparation of antistatic UV ink
[0053] The UV resin prepolymer, acrylate monomer, UV photoinitiator, the surface silver-plated carbon nitride nanoparticle dispersion prepared in Example 1 and the control group, the leveling agent, the wetting agent and the defoaming agent are mixed in proportion (the proportion is shown in Table 2-4) to prepare an antistatic UV ink. After that, the obtained ink is coated on a PET film by screen printing, and reacted for 1 hour under ultraviolet light to prepare an antistatic ink coating on the surface of the PET film. The surface resistance tester is used to test according to the national standard GB / T1410-2006.
[0054] Table 2 Specific examples of antistatic ink of Example 1:
[0055]
[0056] In the table, A, B, and C represent different UV resin prepolymers, and the mass unit is g.
[0057] Table 3 Specific examples of antistatic inks for the control group:
[0058]
[0059]
[0060] Table 4 Antistatic properties of UV inks in the control group and the experimental group (surface resistance between 106-109 has antistatic properties)
[0061]
[0062]
[0063] IV. Results
[0064] Compared with the control group 1, under the same other conditions, the experimental group differs only in that the experimental group uses silver quantum dots to be directly generated on the surface of oxygen-doped carbon nitride. The antistatic properties of the experimental group are improved. Analysis shows that there are no organic molecules between the silver quantum dots and the oxygen-doped carbon nitride, and the electronic conductivity between the oxygen-doped carbon nitride and the silver quantum dots is excellent.
[0065] Compared with the control group 2, under the same other conditions, the only difference between the experimental group and the control group 2 is that the experimental group uses oxygen-doped carbon nitride, and the antistatic performance is greatly improved. Analysis shows that the conventional carbon nitride has fewer sites for the adsorption of silver ions on the surface, so the amount of silver quantum dots loaded on the surface is small, and most of the silver quantum dots exist alone. The oxygen-doped carbon nitride has more sites for the adsorption of silver ions on the surface, the amount of silver quantum dots loaded on the surface is greater, and the conductivity is excellent.
[0066] The film-forming ability of the experimental group and the control group 1 is stronger than that of the control group 2, which shows that oxygen-doped carbon nitride can improve the film-forming ability of the product compared with conventional carbon nitride.
Claims
1. Antistatic ink, characterized in that: In parts by weight, it comprises: UV resin prepolymer: 10-20 parts; Acrylate monomer: 9-20 parts; Butyl acrylate: 8-20 parts; Photoinitiator: 0.4-0.7 parts; Surface-coated silver carbonitride nanoparticle dispersion: 35-70 parts, wherein the carbonitride is oxygen-doped carbon nitride, the plated silver is silver quantum dots, and there is no organic molecule between the silver quantum dots and the oxygen-doped carbon nitride; Other appropriate additives.
2. The antistatic ink according to claim 1, characterized in that: The surface silver-plated carbon nitride nanoparticle dispersion is prepared by plating silver quantum dots on the surface of oxygen-doped carbon nitride through a silver plating step. The silver plating step is to first adsorb silver ions on the surface of the oxygen-doped carbon nitride, and then generate silver quantum dots in situ on the surface of the oxygen-doped carbon nitride.
3. The antistatic ink according to claim 1, characterized in that: The other appropriate amount of additives include leveling agents, wetting agents and defoaming agents.
4. A method for preparing an antistatic ink, characterized in that: Here are the steps: S1: preparing UV light-curable resin prepolymer; S2: preparing oxygen-doped carbonitride nanoparticles, adding the obtained nanoparticles, tyrosine, and silver ammonia solution into deionized water, gradually adding glucose after ultrasonic dispersion, then ultrasonically dispersing, centrifugally drying, adding ethyl acetate containing polyvinylpyridine, and ultrasonically dispersing to obtain a suspension; S3: The prepared UV light-curable resin prepolymer, acrylate monomer, UV photoinitiator, prepared suspension, leveling agent, wetting agent and defoaming agent are mixed in proportion to prepare antistatic UV ink.
5. The method for preparing the antistatic ink according to claim 4, characterized in that: The method for preparing a UV light-curing resin prepolymer is as follows: adding measured amounts of polyethylene glycol, polypropylene glycol, 2,2-dihydroxymethylpropionic acid, isophorone diisocyanate and dibutyltin dilaurate into a container, slowly heating the container to 80°C while stirring, and reacting at a constant temperature for 6 hours; then cooling the container to 60°C, adding measured amounts of hydroxyethyl acrylate, and reacting at a constant temperature for 4 hours; then cooling the container to room temperature to obtain a UV light-curing polyurethane prepolymer.
6. The method for preparing the antistatic ink according to claim 5, characterized in that: The method for preparing oxygen-doped carbonized nitrogen nanoparticles is as follows: weigh melamine and put it into a muffle furnace, heat it to 400°C without nitrogen protection, and react at a constant temperature for 8 hours. After the reaction is completed, reduce the temperature to room temperature to obtain oxygen-doped carbonized nitrogen nanoparticles.
7. The method for preparing the antistatic ink according to claim 6, characterized in that: The preparation method of the suspension pair is as follows: oxygen-doped carbon nitride nanoparticles, tyrosine and a 10wt% silver ammonia solution are added to deionized water, ultrasonically dispersed, and then glucose is gradually added. After the addition is complete, ultrasonication is continued, and then centrifugation is performed to obtain a precipitate. The obtained precipitate is vacuum-dried at 60°C, and ultrasonically dispersed in 1000ml of ethyl acetate containing 0.1wt% polyvinylpyridine for 2h to obtain a suspension.
8. The method for preparing the antistatic ink according to claim 7, characterized in that: The molecular weight of the polyethylene glycol is between 400-2000, and the molecular weight of the polypropylene glycol is between 400-2000.